The Relationship Between Anemia and Nutritional Status with the Occurrence of Fatigue in Children with Cancer Undergoing Chemotherapy at Dharmais Cancer Hospital in Jakarta - Purwati, Nyimas Heny; Natashia, Dhea; Wahyuni, Emmy Putri; Dais, Exsos Grend; Lusty, Junita; Ruriwinita, Ruriwinita; Sofyan, Evi; Fitriana, Anantusia; Karwati, Eti; Fitriyati, Fitriyati; Mursiah, Mursiah (Universitas Muhammadiyah Yogyakarta, 2023)
Background: The challenge of fatigue significantly affects children undergoing cancer treatment, impacting their overall well-being and quality of life. Unlike their healthy counterparts, pediatric cancer patients grapple with the demanding impacts of chemotherapy, leading to anemia and nutritional deficiencies that exacerbate fatigue. Beyond fatigue, chemotherapy alters appetite, nutrient utilization, and mental function. Fatigue's multidimensional impact, marked by reduced energy and increased need for rest, can detrimentally affect the quality of life for pediatric patients. Understanding these challenges is essential for devising tailored strategies that comprehensively address the unique needs of children undergoing cancer treatment, enhancing their overall well-being and quality of life.Objective: This research aims were to determine the relationship between anemia and nutritional status with the occurrence of fatigue in children with cancer undergoing chemotherapy at Dharmais Cancer Hospital in Jakarta.Methods: An analytical cross-sectional study conducted in August 2022 included a sample of 24 children selected through accidental sampling. Demographic and disease characteristics, such as age, gender, cancer type, cancer stage, and treatment duration, were collected through a questionnaire. Anemia was determined by hemoglobin levels (12 mg/dl), and nutritional status was assessed using Body Mass Index. Fatigue was measured with tailored instruments for different age groups: the Parent Fatigue Scale (PFS) for children under 7 years and the Child Fatigue Scale (CFS) for those aged 7 years and older. Statistical analyses included univariate assessment, bivariate analysis with the chi-square test, and logistic regression.Results: Demographic analysis revealed a predominantly male sample (70.8%) with a significant adolescent presence (41.7%) and a prevalence of leukemia (37.5%). Most participants were in early cancer stages (58.3%), undergoing treatment for over a year (62.5%). Anemia was common (54.2%), and 58.3% were underweight. High fatigue prevalence was observed (62.5%). Chi-square analysis found no significant gender or cancer stage differences in fatigue. Age and treatment duration showed no significant associations with fatigue. Logistic regression revealed a significant association between anemia and fatigue in the first model (p = 0.022, Exp. B = 0.104). The second model, incorporating nutritional status, showed a non-significant relationship with anemia but a notable association with normal nutritional status and fatigue (p = 0.022, Exp. 0.059). This underscores the crucial role of nutritional interventions in mitigating fatigue.Conclusion: This study highlights a significant relationship between anemia and nutritional status with fatigue in children undergoing chemotherapy. These findings underscore the importance of considering anemia and nutritional interventions when providing care to pediatric cancer patients undergoing chemotherapy. Nurses play a vital role in addressing these concerns and enhancing the overall well-being of children with cancer.